Characterization of Acidovorax citrulli strains isolated from solanaceous plants. (12th July 2020) - Chalupowicz, Laura; Reuven, Michal; Dror, Orit; Sela, Noa; Burdman, Saul; Manulis‐Sasson, Shulamit
Abstract: Acidovorax citrulli is the causal agent of bacterial fruit blotch disease of cucurbits. Strains of this pathogen are distributed into two major groups: Group I strains have been mainly isolated from melon and other non‐watermelon cucurbits, while Group II strains have been mainly recovered from watermelon. Here we report the characterization of strains T1 and EP isolated from diseased tomato and eggplant plants, respectively, and further confirmed to belong to A . citrulli species. Based on PCR, PFGE, and rep‐PCR, these strains showed high similarity to the Group II strain 7a1. Sequencing and comparative analyses revealed that the genomes of T1 and EP aligned with that of the Group II model strain AAC00‐1, over 97.88% and 99.22%, respectively. The virulence of T1, EP, and 7a1 determined on tomato, eggplant, and watermelon was similar and significantly higher than that of Group I strain M6. In contrast, M6 was more virulent on melon. Expression levels of seven virulence genes measured 24 hr after inoculation of tomato, eggplant, watermelon, and melon showed that the expression pattern was generally similar in strains 7a1, T1, and EP, whereas for M6 the expression was high only on melon. Overall, our results indicate that the solanaceous strains belong to Group II. To the best of our knowledge, this is the first study that reports characterization of A . citrulli strains isolated from solanaceous species. The fact that A . citrulli is able to naturally colonize and cause disease in non‐cucurbit crops poses additional challenges for management of this important pathogen. Abstract : Strains isolated from diseased tomato and eggplant plants showed high similarity to group II strains of Acidovorax citrulli by sequencing, measuring virulence, and gene expression on solanaceous and cucurbit plants.